Formulation of Longgi Flour-Based Brownies Substituted with Tilapia Flour - Shindy H Manteu; Nikmawatisusanti Yusuf; Lukman Mile (Faculty of Fishery and Marine Sciences - Universitas Negeri Gorontalo, 2019)
This study aims to formulate Longgi (Xanthosoma sagitifolium) flour-based brownies substituted by tilapia (Oreochromis niloticus) flour. The research consists of two stages: a preliminary study and the main study. In the preliminary study is that the manufacture of tilapia flour and Longgi brownies. The main study is the formulation stage. Organoleptic analysis of the data used was Kruskal-Wallis test with a parameter that is the taste, texture, aroma, color and appearance. If the result of significant (p